Investigating Essential Characteristics of Scientific Practices in Elementary Science Learning Environments: The Practices of Science Observation Protocol (P‐SOP). (5th April 2013) - Forbes, Cory T.; Biggers, Mandy; Zangori, Laura
Abstract : Within the field of science education, there remains little agreement as to the definition and characteristics of classroom inquiry. The emerging emphasis on scientific practices in science education reform discourse is underpinned by a need to better articulate the constituent elements of inquiry‐based science. While a small number of observation‐based instruments have been developed to characterize science learning environments, few are explicitly aligned with theoretical constructs articulated by the National Research Council and/or have been substantially field‐tested. We employ a newly developed instrument, the Practices of Science Observation Protocol (P‐SOP), to investigate essential features of inquiry and scientific practices in which early learners engage in elementary classrooms. This research is part of a multiyear professional development program designed to support elementary teachers (K‐5) in a large, urban school district to learn to better engage students in scientific practices. Project teachers video‐recorded enacted science lessons ( n = 124) which were used as data. Findings illustrate both essential features of inquiry and scientific practices observed in elementary classrooms, as well as establish the P‐SOP as a valid and reliable observation protocol. These findings have important implications for the design of elementary science learning environments and associated research and development efforts in the field.